2007
DOI: 10.1007/s10646-006-0119-8
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine disrupting compounds and echinoderms: new ecotoxicological sentinels for the marine ecosystem

Abstract: Echinoderms are valuable test species in marine ecotoxicology and offer a wide range of biological processes appropriate for this approach. In spite of this potential, available data in literature are still rather limited, particularly with regard to the possible effects of endocrine disrupter compounds (EDCs). This review presents echinoderms as useful models for ecotoxicological tests and gives a brief overview of the most significant results obtained in recent years, particularly in the context of the COMPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 54 publications
(48 reference statements)
2
45
0
Order By: Relevance
“…Past and recent investigations have identified vertebrate type steroids, i.e. progesterone, testosterone and 17b-estradiol in several echinoderm species (see for literature Sugni et al 2007). In crustaceans steroids with structural similarities to those of vertebrates could be identified (Fingerman et al 1993, Lafont & Mathieu, 2007, LeBlanc, 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Past and recent investigations have identified vertebrate type steroids, i.e. progesterone, testosterone and 17b-estradiol in several echinoderm species (see for literature Sugni et al 2007). In crustaceans steroids with structural similarities to those of vertebrates could be identified (Fingerman et al 1993, Lafont & Mathieu, 2007, LeBlanc, 2007.…”
Section: Discussionmentioning
confidence: 99%
“…A physiological role for these hormones in this species is suggested by variations of their levels detected during exposure experiments to ED contaminants (Lavado et al 2006a). This appears to be correlated with dysfunctions of gametogenesis (Sugni et al 2008) and regeneration processes (Barbaglio et al 2006;Sugni et al 2007). In the present paper we report variations registered in T and E2 levels during the reproductive cycle of A. mediterranea.…”
Section: Hormone Levelsmentioning
confidence: 99%
“…Tortonese (1965) reported that this species reproduces all through the year, with a maximum intensity in spring and summer. In the last 10 years A. mediterranea has attracted interest due to studies on arm regeneration, its use as developmental model for basic biology studies and as an ecotoxicological model for applied biology studies related to the effects of endocrine disrupters (ED) Candia Carnevali 2005;Barbaglio et al 2006;Sugni et al 2007). In view of this background, there is a need to describe the reproductive biology of this representative mediterranean species, with the ultimate aim of explaining in depth morphological and physiological aspects correlated with gametogenesis, and to enlarge the potential usefulness of this new ecotoxicological model.…”
Section: Introductionmentioning
confidence: 99%
“…Echinoderms have been used as biological indicators and biomarkers of marine contamination, with many extensive studies undertaken over the years. They are useful bioindicators due to their abundance, 20 wide distribution, ecological relevance, benthic behaviour, rapid response and high sensitivity to the presence of many types of pollutants [13]. About its salinity tolerance, echinoderms are commonly considered to be strictly marine species.…”
Section: Introductionmentioning
confidence: 99%